Evaluation of rheological and fluid loss properties of Nigerian bentonite using periwinkle and mucuna solannie. Issue 1 (1st January 2021) - Chinwuba, Igwilo K.; Nnaemeka, Uwaezuoke; Miracle, Ukaka C.; Vivian, Amaefule C.; Bala, Zakka S.
Abstract: Nigerian bentonite has low fluid loss control and poor rheological properties which are key API specifications. Foreign and imported bentonites are sodium-based, while local bentonites are calcium-based, and there is a need for beneficiation. The periwinkle shell used for fluid loss control and Mucuna solannie for rheology are abundant. The elemental compositions and the rheology and fluid loss of the samples were determined by the use of 15 g and 30 g, respectively, of bentonite. Fluid loss, rheology and YP/PV measurements were conducted on local and foreign bentonites to justify the need for beneficiation. With 15 g and 30 g of local bentonite, 27 ml and 11 ml, 600 rpm readings of 18 and 34, with 1.6 and 3.7 were obtained for fluid loss, rheology and YP/PV, respectively. The beneficiated local bentonite with periwinkle and Mucuna solannie gave acceptable results at 4 g-5 g concentrations, with slight deviations observed in rheology measurements. Also, 14 ml and 12 ml, 600 rpm readings of 23 and 26, with 0.85 and 0.6, respectively, for fluid loss, rheology and YP/PV were observed at 4 g-5 g. However, this research work improved the quality of local bentonite using periwinkle shell and Mucuna solannie, with 7 g of each in 250 ml water as projected optimum amounts, in order to make it more suitable for drilling and attain API specification at 600 rpm reading of 30. The results proved that the beneficiated local bentonite is able to compete with foreign bentonite and also met API specifications when added in the right quantities. Another approach to beneficiation other than atomic exchange has been highlighted.